2019
DOI: 10.1093/cid/ciz039
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes With High-dose Isoniazid in Multidrug-resistant Tuberculosis Treatment in Haiti

Abstract: We report outcomes for a cohort of patients with multidrug-resistant tuberculosis who received high-dose isoniazid in Haiti. Patients who received high-dose isoniazid had a faster time to culture conversion and higher odds of successful outcome, despite high-level isoniazid resistance. This suggests high-dose isoniazid may have effectiveness even with phenotypic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Isoniazid, ethambutol, and prothionamide are included mainly for additional protection of the core drug. High-dose instead of normal-dose isoniazid is preferred because a higher concentration has been shown to overcome low-level resistance and may be particularly useful for patients with thioamide cross-resistance [19,20]. Prothionamide is given only during the intensive phase to limit frequent gastrointestinal adverse events, often responsible for loss to follow-up.…”
Section: Composition Of the Initial Regimenmentioning
confidence: 99%
“…Isoniazid, ethambutol, and prothionamide are included mainly for additional protection of the core drug. High-dose instead of normal-dose isoniazid is preferred because a higher concentration has been shown to overcome low-level resistance and may be particularly useful for patients with thioamide cross-resistance [19,20]. Prothionamide is given only during the intensive phase to limit frequent gastrointestinal adverse events, often responsible for loss to follow-up.…”
Section: Composition Of the Initial Regimenmentioning
confidence: 99%
“…Published data on the influence of genotype on treatment outcomes of RsHr-TB are conflicting, study from Vietnam, suggest that katG mutations and not inhA are associated with unfavorable treatment outcomes [33]. Whereas in a study from South Africa, no evidence was found suggesting that specific isoniazid resistance conferring mutations are associated with poor treatment outcomes, and results showed that patients with katG mutations had greater odds of successful outcome when treated with high-dose isoniazid compared to those who received standard dose [34].Few studies have also evaluated the effectiveness of high-dose isoniazid in patients with DRTB and limited data available suggest clinical benefit without a higher toxicity [35,36]. A recent study has demonstrated that high dose INH in MDR patients with inhA mutations has similar magnitude of bactericidal activity as with standard doses in drug-susceptible TB patients [37].…”
Section: Plos Onementioning
confidence: 99%
“…A one-dose-fits-all dosing approach must be carefully weighed against the risk of toxicity in patients with slow NAT2 (N-acetyltransferase 2) metabolizer status, whose INH concentrations can be up to threefold higher than those in fast acetylators, and the consequences of potential differences in efficacy related to mutation type. Accumulating indirect evidence that HD-INH has activity against strains with katG mutations (which tend to produce higher minimum inhibitory concentrations in vitro) needs confirmation (3)(4)(5). In the next phase of INHindsight, we will measure the early bactericidal activity of HD-INH (15-20 mg/kg) in patients with pulmonary TB caused by Mycobacterium tuberculosis strains with katG mutations.…”
Section: From the Authorsmentioning
confidence: 99%